Simulated Herbivory Affects the Volatile Emissions of Oak Saplings, while Neighbourhood Affects Flavan-3-ols Content of Their Leaves - Molleman, Freerk; Mandal, Manidip; Sokół-Łętowska, Anna; Walczak, Urszula; Volf, Martin; Mallick, Soumen; Moos, Martin; Vodrážka, Petr; Prinzing, Andreas; Mezzomo, Priscila (Journal of chemical ecology, 2024)
To what extent particular plant defences against herbivorous insects are constitutive or inducible will depend on the costs and benefits in their neighbourhood. Some defensive chemicals in leaves are thought to be costly and hard to produce rapidly, while others, including volatile organic compounds that attract natural enemies, might be cheaper and can be released rapidly. When surrounding tree species are more closely related, trees can face an increased abundance of both specialist herbivores and their parasitoids, potentially increasing the benefits of constitutive and inducible defences. To test if oaks (Quercus robur) respond more to herbivore attacks with volatile emission than with changes in leaf phenolic chemistry and carbon to nitrogen ratio (C: N), and whether oaks respond to the neighbouring tree species, we performed an experiment in a forest in Poland. Oak saplings were placed in neighbourhoods dominated by oak, beech, or pine trees, and half of them were treated with the phytohormone methyl jasmonate (elicitor of anti-herbivore responses). Oaks responded to the treatment by emitting a different volatile blend within 24 h, while leaf phenolic chemistry and C: N remained largely unaffected after 16 days and multiple treatments. Leaf phenolics were subtly affected by the neighbouring trees with elevated flavan-3-ols concentrations in pine-dominated plots. Our results suggest that these oaks rely on phenols as a constitutive defence and when attacked emit volatiles to attract natural enemies. Further studies might determine if the small effect of the neighbourhood on leaf phenolics is a response to different levels of shading, or if oaks use volatile cues to assess the composition of their neighbourhood.
Keywords: cyklopentany; flavonoidy; Animals; Cyclopentanes; Volatile Organic Compounds; Nitrogen; listy rostlin; Herbivory; oxylipiny; Flavonoids; Polyphenols; Plant Leaves; dub (rod); Acetates; Quercus; Oxylipins; acetáty; Intra-specific Variation; býložravci; Tritrophic Interactions; zvířata; těkavé organické sloučeniny; VOCs; Methyl Jasmonate; Carbon; uhlík; dusík